The Nature Of US-Italian Relations Under The Fascist Rule In Italy (1922 - 1923) - Ibrahim Al-Quraishi, Muhammad Yusuf; Sultan, Wasumiy Sweileh (Journal of Tikrit University for Humanities, 2023)
Italy’s participation in the First World War and its exit from it contributed to obtaining few gains that were not commensurate with the size of the losses it provided in the war, from the deterioration of the internal conditions and the spread of discontent among the Italian people, whose suffering increased with the passage of days, and the inability of the political system based on solving many problems Italy suffered after the war, as a result of political instability and many differences between political parties, as well as bad economic conditions that were reinforced by the spread of unemployment. And that the democratic system would prevail in that country, and that Italy’s economic conditions would improve in order to hasten to overcome its political problems, especially after Mussolini announced his desire to establish a system of friendship and cooperation with Western countries, and expressed his hope that Italian-American relations would witness a close rapprochement in the political and economic fields.